Urgensi dan Implementasi Auditing Keuangan dalam Lembaga Pendidikan Islam - Bayo Hadomuan Tanjung; Amalliya Nurjannah; Heni Noviarita; Romlah; Ahmad Fauzan (Kartika: Jurnal Studi Keislaman, 2025)
Financial auditing in Islamic educational institutions is a vital instrument that functions not only as an internal control mechanism but also as a guarantee of accountability, transparency, and efficiency in managing funds entrusted by the Muslim community. These funds such as zakat, infaq, sadaqah, and waqf, carry profound spiritual and social significance, thus requiring financial management that adheres to both sharia principles and professional standards. This article aims to examine the urgency of financial auditing in Islamic education, identify the core principles that must guide auditing practices, such as trustworthiness (amanah), justice (ʿadl), excellence (ihsan), and transparency and analyze the implementation and challenges of auditing practices in contemporary Islamic educational management. Using a literature review approach, this study explores references from nationally and internationally accredited academic journals, as well as classical and contemporary Islamic literature. The findings indicate that financial auditing is not merely a technical necessity but also a moral responsibility embedded in the financial management of Islamic education. Therefore, strengthening audit systems grounded in sharia principles is an integral part of realizing credible, transparent, and sustainable governance in Islamic educational institutions.